Three-Dimensional Printing Strategies for Irregularly Shaped Cartilage Tissue Engineering: Current State and Challenges - Wang, Hui; Wang, Zhonghan; Liu, He; Liu, Jiaqi; Li, Ronghang; Zhu, Xiujie; Ren, Ming; Wang, Mingli; Liu, Yuzhe; Li, Youbin; Jia, Yuxi; Wang, Chenyu; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Although there have been remarkable advances in cartilage tissue engineering, construction of irregularly shaped cartilage, including auricular, nasal, tracheal, and meniscus cartilages, remains challenging because of the difficulty in reproducing its precise structure and specific function. Among the advanced fabrication methods, three-dimensional (3D) printing technology offers great potential for achieving shape imitation and bionic performance in cartilage tissue engineering. This review discusses requirements for 3D printing of various irregularly shaped cartilage tissues, as well as selection of appropriate printing materials and seed cells. Current advances in 3D printing of irregularly shaped cartilage are also highlighted. Finally, developments in various types of cartilage tissue are described. This review is intended to provide guidance for future research in tissue engineering of irregularly shaped cartilage..